2009
DOI: 10.1186/1476-511x-8-25
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid and peanut oil high in oleic acid reverse the inhibitory effect of insulin production of the inflammatory cytokine TNF-α both in vitro and in vivo systems

Abstract: Background: Chronic inflammation is a key player in pathogenesis. The inflammatory cytokine, tumor necrosis factoralpha is a well known inflammatory protein, and has been a therapeutic target for the treatment of diseases such as Rheumatoid Arthritis and Crohn's Disease. Obesity is a well known risk factor for developing non-insulin dependent diabetes melitus. Adipose tissue has been shown to produce tumor necrosis factor-alpha, which has the ability to reduce insulin secretion and induce insulin resistance. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
168
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(189 citation statements)
references
References 42 publications
11
168
0
7
Order By: Relevance
“…Oleic acid has also shown a beneficial effect on insulin sensitivity, adipocyte glucose transport and prevents T2D [62][63][64][65].…”
Section: Glucose-and Oleic Acid Uptake In Skeletal Muscle Cells and Lmentioning
confidence: 99%
“…Oleic acid has also shown a beneficial effect on insulin sensitivity, adipocyte glucose transport and prevents T2D [62][63][64][65].…”
Section: Glucose-and Oleic Acid Uptake In Skeletal Muscle Cells and Lmentioning
confidence: 99%
“…FAMEs including oleic acid and α-linolenic acid were identified as the potential biomarkers of T2DM for their powerful discriminant ability of T2DM patients from healthy controls [23]. Addition of oleic acid in diet in Type 2 diabetic patients reduced insulin resistance and restored endothelium-dependent vasodilatation [24] and oleic acid was found to be effective in reversing the inhibitory effect in insulin production of the inflammatory cytokine tumor necrosis factor alpha (TNF-α) [25]. Studies have also shown that omega-3 fatty acids such as α-linolenic acid offer a direct or indirect reno-protective effect in diabetes patients [26].…”
Section: Gc-ms Analysis Of Fractionsmentioning
confidence: 99%
“…Thus, there is interest in producing and promoting the consumption of high-oleic peanuts to improve shelf-life without promoting the risk of obesity and its complications (6). High oleic acid peanuts may also reduce the negative metabolic effects of dietary saturated fatty acids (SFA) (8,9).…”
Section: Introductionmentioning
confidence: 99%